Medulloblastomics revisited: biological and clinical insights from thousands of patients - Hovestadt, Volker; Ayrault, Olivier; Swartling, Fredrik J.; Robinson, Giles W.; Pfister, Stefan; Northcott, Paul A. (Nature reviews. Cancer, 2019)
This Review discusses recent genomic, epigenomic, transcriptomic and proteomic profiling studies of human medulloblastoma that have advanced our understanding of its disease subgroups. These efforts have provided new insights into the diverse biology of medulloblastomas that will hopefully lead to improved diagnosis and therapy.